Evaluasi Kinerja Dosen Prodi Pendidikan Teknik Informasi pada Semester Ganjil Tahun Akademik 2022/2023 - Elyakim Nova Supriyedi Patty; Irhas Irhas (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This article discusses the importance of lecturer professionalism in achieving national education goals in universities, especially in the Informatics Engineering Education Study Program at Bumigora University. The professionalism of lecturers includes pedagogic, professional, personality, and social competencies, which play a role in creating a quality educational environment. This study explains how the evaluation of lecturer performance is carried out through questionnaires filled out by students and how the results of this evaluation are used to motivate lecturers to improve the quality of education. The evaluation results show that the level of student satisfaction with the overall performance of lecturers is very good, but there is still room for improvement. Social Competence was rated highest, while Personality Competence had the lowest level of satisfaction. These results show that the professionalism of lecturers in terms of social interaction can be improved. Evaluation of lecturer performance is an important step in ensuring the quality of higher education and encouraging lecturers to continuously improve their professionalism. This article concludes that efforts to improve the professionalism of lecturers need to continue so that higher education remains of high quality and in accordance with national education goals